Enlarged perivascular and extraperivascular (pericellular and neuropil) edematous spaces in the brain tissue during human sepsis-associated encephalopathy - Shuliatnikova, T. V.; Tumanskyi, V. O.; Tumanska, L. M.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович; Туманська, Любов Михайлівна (My University, 2024)
Sepsis-associated encephalopathy (SAE) is defined as diffuse cerebral dysfunction during sepsis without direct brain infection, which clinically features by alteration of consciousness up to coma.